THE MASS MEDIA’S LANGUAGE STYLES: ITS POWER AND APPROPRIATENESS FROM THE PERSPECTIVE OF SYSTEMIC FUNCTIONAL LINGUISTICS - Sukma Septian Nasution (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
The role of mass media is inevitably significant for people’s everyday life. As one of mass media, newspaper is very effective not only in informing the readers but also in influencing their principles and belief regarding to certain issues. However, texts published in newspapers potentially goes unsuitable for the targeted readers making its significance in informing and influencing less optimal. Accordingly, it is necessary to research the language styles of newspapers to optimize its power of significance in influencing the potential or targeted readers. This is a descriptive analysis study employing systemic functional linguistics (SFL) in analyzing the language styles of texts published by two popular mass media; The Jakarta Post and National Geographic. The analysis tools underpinned by SFL used in this study are the lexical system of congruency, lexicogrammar of complex-simplex clauses, conjunctive relations, and complexity of verbal and nominal groups of the news. The results show that (1) the targeted readers of the news are adult; (2) the use of incongruent lexis, internal conjunction, simple clause, complex group both verbal and nominal, and generic participant are more frequently employed; accordingly (3) written style is employed more often than spoken style. The findings drive to the conclusions that most of the news’ language styles go appropriate to the targeted readers. It means that its power to inform and influence the readers goes optimal. However, the linguistic techniques need improving in order the texts sound more intelligible to the targeted readers.